THE IMPLEMENTATION OF 'TYPOMAN GAME' TO TEACH VOCABULARY (Descriptive Qualitative Research) - kholil, mahmud (JELLE, 2024)
Mastery of English vocabulary is crucial for high school students' communication skills and academic success. However, some students in Indonesia face challenges in mastering English vocabulary, primarily due to a lack of exposure during their elementary school years. Therefore, this research aims to investigate the implementation of the edutainment game "Typoman Game" as a tool to enhance students' vocabulary skills at MTS Salafiyah Yapensa Jenggot. This study adopts a descriptive qualitative research design, collecting data through direct observation and in-depth interviews with students and English teachers. Data were analyzed thematically to understand the effectiveness of the 'Typoman Game' in improving students' vocabulary mastery. The implementation of the 'Typoman Game' in the learning process involved collaboration between teachers and researchers and demonstrated its effectiveness in enhancing students' vocabulary skills. Challenges such as game complexity and time constraints were addressed by providing guidance and adapting game content. Nonetheless, high levels of student engagement and interaction proved the game's success as a learning tool. This research concludes that the 'Typoman Game' is effectively used in English vocabulary learning in high schools, despite facing some challenges. Through collaboration between teachers and researchers, the game can enhance students' interest in language learning and create meaningful learning experiences.Keywords: Typoman Game, English vocabulary, edutainment, high school students, innovative learning methods Penguasaan kosakata bahasa Inggris merupakan hal penting bagi siswa sekolah menengah untuk kemampuan komunikasi dan kesuksesan akademis. Namun, beberapa siswa di Indonesia menghadapi tantangan dalam menguasai kosakata bahasa Inggris, terutama karena kurangnya paparan selama tahun-tahun pendidikan dasar mereka. Oleh karena itu, penelitian ini bertujuan untuk menyelidiki implementasi permainan edutainment "Typoman Game" sebagai alat untuk meningkatkan keterampilan kosakata siswa di MTS Salafiyah Yapensa Jenggot. Penelitian ini mengadopsi desain penelitian kualitatif deskriptif dengan mengumpulkan data melalui observasi langsung dan wawancara mendalam dengan siswa dan guru Bahasa Inggris. Data dianalisis secara tematik untuk memahami efektivitas permainan 'Typoman Game' dalam meningkatkan penguasaan kosakata siswa. Implementasi permainan 'Typoman Game' dalam proses pembelajaran melibatkan kerjasama antara guru dan peneliti serta menunjukkan efektivitasnya dalam meningkatkan keterampilan kosakata siswa. Tantangan seperti kompleksitas permainan dan batasan waktu diatasi dengan memberikan bimbingan dan menyesuaikan konten permainan. Meskipun demikian, tingkat keterlibatan siswa dan interaksi yang tinggi membuktikan keberhasilan permainan sebagai alat pembelajaran. Penelitian ini menyimpulkan bahwa permainan 'Typoman Game' efektif digunakan dalam pembelajaran kosakata Bahasa Inggris di sekolah menengah, meskipun menghadapi beberapa tantangan. Dengan kolaborasi antara guru dan peneliti, permainan ini dapat meningkatkan minat siswa dalam pembelajaran bahasa dan menciptakan pengalaman belajar yang bermakna. Kata kunci: Typoman Game, kosakata bahasa Inggris, edutainment, siswa sekolah menengah, metode pembelajaran inovatif.